Clones reactive to apoptotic cells and specific chemical adducts are prevalent among human thymic B cells - Hertel, Andrea; Aguiar, Talita; Mashiko, Shunya; Núñez, Sarah; Moore, Carolina; Gao, Baoshan; Ausmeier, Mattea; Roy, Poloumi; Zorn, Emmanuel (Frontiers in Immunology, 2024)
Thymus resident B cells were described more than 40 years ago. In early human life, these cells are found predominantly in the medulla and overwhelmingly display an unswitched IgM+ phenotype. The reactivity of thymic IgM B cells, however, is still unclear. Here, we generated 120 IgM-producing B cell clones from 3 separate thymus specimens obtained from infant, adolescent, and adult donors. Using flow cytometry and a unique high-dimensional ELISA platform, we investigated the clones' reactivity to apoptotic cells as well as to common chemical adducts exposed on modified amino acids and other macromolecules. Regardless of the age, approximately 30-40 % of thymic IgM B cells reacted to apoptotic cells. Further, 30-40% displayed reactivity to at least one adduct, including malondialdehyde, Homocysteine, and NEDD 8. Four distinct reactivity patterns were identified through this profiling. Notably, a significant association was observed between reactivity to apoptotic cells, and to one or more adducts, suggesting that the same determinants were recognized in both assays. Additionally, thymic IgM B cells reactive to adducts were more likely to recognize intra-nuclear or intracytoplasmic structures in Hep-2 cells as revealed by immunofluorescence staining. Collectively, our findings suggest that thymic IgM B cells actively uptake apoptotic bodies and cellular debris in the medulla by binding specific chemical adducts. This mechanism could underpin their antigen-presenting function and further support their role in T-cell negative selection.